Risk factors of stunting and wasting in Somali pre-school age children: results from the 2019 Somalia micronutrient survey - William E. S. Donkor; Joshua Mbai; Fatmata Sesay; Sundus Ibrahim Ali; Bradley A. Woodruff; Shuaib Mohamoud Hussein; Kheyriya Mohamed Mohamud; Ahmed Muse; Warsame Said Mohamed; Abdullahi Muse Mohamoud; Farhan Mohamed Mohamud; Nicolai Petry; et al. (BMC, 2022)
Abstract Background Stunting and wasting in children less than 5 years of age are two key indicators of child malnutrition. Reducing their prevalence is a priority of the global public health community and for Somalia, a country suffering complex humanitarian emergencies such as drought, flooding, conflict and large-scale displacements. Methods Data from the nationally representative cross-sectional Somalia Micronutrient Survey (SMS 2019) on 1947 children were analyzed to assess the prevalence and potential risk factors of stunting and wasting. Bivariate and multivariable analyses were conducted separately for children 0-5 months and 6-59 months, and population attributable fractions were calculated using adjusted risk ratios produced by Poisson regression models. Results Among the 1947 children, the prevalence of stunting and wasting were 17.2% (95% CI: 15.0, 19.6) and 11.0% (95% CI: 9.3, 12.9), respectively. Among children 6-59 months of age, those residing in severely food insecure households had a higher risk of stunting (adjusted risk ratio [aRR] 1.47; CI: 1.12, 1.93) compared to those in food secure households. This risk of stunting was also higher in children with inflammation (aRR 1.75; CI: 1.35, 2.25) and iron deficiency (ID) (aRR 2.09; CI: 1.58, 2.80). For wasting, a dose-response relationship was found with household wealth, with the risk of wasting increasing significantly as the household wealth quintile decreased. On the other hand, the risk of wasting was lower in iron-deficient children (aRR 0.69; CI: 0.49, 0.98) than in iron-replete children. Among children 0-5 months of age no variables remained statistically significantly associated with stunting in the multivariable analysis. Wasting, however, was more common in children with recent diarrhea (aRR 3.51; CI: 1.68, 7.36). Conclusions Nutritional status of children in Somalia may be improved by prevention of diarrhea and other infections and improvements in household food security.